Educação Financeira no livro didático de matemática dos anos finais do ensino fundamental - Ferreira, Nathália Martins (2021)
Financial resources have always been of outstanding importance in the lives of individuals; at present the influence of the "currency" has been enhanced by socially assumed values, and the need for attitudes that mitigate the impacts of indebtedness arises. Awareness and knowledge are indispensable tools to mitigate the impacts of difficulty in owning and managing financial resources. Financial Education (FE) assists in the well-being of people, avoids staggering debts and ensures a quieter life, as well as allowing strategies of economic and social domination to be recognized. This work presented an analysis of a collection of the National Educational Book Program (PNLD) 2020, aiming to understand how the contents that work Financial Education are presented in the Final Years of Elementary Education. In this way the qualitative approach was used, through the Content Analysis, where were investigated the activities of RF that were inserted in the collection "The conquest of Mathematics." The Analysis of this collection has made it possible to identify some important features of the activities. The contents are worked in an aroused way, without reflection of the concepts addressed in the few pages of each volume working the RU. Critical Financial Education is not only to present content to students, but also to encourage them to apply it on a daily basis and to be citizens who care about natural resources that are limited and that there is no sustainable development.